Obesity prevalence and associated factors in Brazilian population (Research, Society and Development, 2023)
Obesity is defined as a complex multifactorial disease, resulting from excess adiposity harmful to health. It is also considered a risk factor for other pathologies, especially chronic non-communicable diseases (NCDs). The purpose of the study was to assess the prevalence of obesity and associated factors in Brazil and in Brazilian regions. Data from the 2019 National Health Survey (PNS 2019) were used. The prevalence of obesity was verified and association and risk tests were performed with sociodemographic, dietary, physical perception, health and chronic disease indicators. The prevalence of obesity in the country was 20.13%, with the highest frequencies in females and in more industrialized regions. In addition, obesity rates are as well as between diagnostic factors and worse quality of life or with the perception of chronic disease. It is concluded that it is important that they seek to verify the prevalence of obesity studies and factors are to guide public policies that impact on the increase of overweight and associated in the country.